IDENTIFICATION OF Leishmania PARASITES IN CLINICALSAMPLES OBTAINED FROM CUTANEOUS LEISHMANIASISPATIENTS USING PCR TECHNIQUE IN IRAQ - Qader, Abdullah; Abood, Mushriq; Bakir, Tural (Iraqi Journal of Science, 2024)
Cutaneous Leishmaniasis (CL) is an endemic disease and one of the majorhealth problems in Iraq. Leishmania major is confirmed as the causative agent of CLin this region. In Al- Qadessia province alone, the recorded total cases of CL were618 from 2005-2007. We aimed to determine the effectiveness of a polymerasechain reaction (PCR) technique for identification and differentiation of theLeishmania parasite in clinical samples. The lesion exudates were collected from 27suspected patients (12 males and 15 females) and used for smear slide preparations,culture on NNN medium then DNA isolation. The isolated DNA was amplified byPCR, including primers selected on repetitive kDNA for identification of aLeishmania subgenus, and the amplified DNA electrophoreses was done. The PCRresults showed that only L. major exists. Our results indicate that the PCR techniqueis sensitive and specific for the detection and differentiation of agents of CL in thisarea.